The Negative Impact of Giving Instant Food to Children: A Review of Literature Studies on Health Risks - Andi Nursiah; Dwi Siyamsih; Anita Lontaan; Hasnidar Hasnidar; Dona Suzana (Oshada, 2025)
This study aims to analyze the negative impacts of instant food consumption on children's health. Instant food is often consumed because of its ease of preparation, but its nutritional content is not balanced. The method used is a review of literature studies from various health journals, nutrition articles, and reports from international health organizations such as WHO. The literature reviewed focuses on the impact of instant food consumption on children's physical and mental health. The results of the study show that instant foods that are high in salt, sugar, fat, and preservatives can cause various health problems, such as obesity, diabetes, hypertension, and cognitive development disorders. In addition, high levels of sodium and trans fat in instant foods can affect the body's metabolic function, increasing the risk of chronic diseases later in life. Lack of fiber intake in instant foods also contributes to digestive problems and lack of essential nutrients for children. Therefore, it is important for parents to be more selective in choosing the food consumed by children. Reducing the consumption of instant foods and replacing them with more nutritious foods is very necessary to support optimal child growth and development